Constant Bit Rate For Video Streaming Over Packet Switching Networks - Khamiss, Nasser N.; Abdullah, Hamsa A. (Nahrain University College of Engineering Journal, 2008)
This paper proposed a technique of bit-rate control for video streaming over constant bit-rate communication channel, where the MPEG-2, standard variable bit-rate (VBR), is adapted to be used as a constant bitrate (CBR). The target image quality and output rate of the video encoder is controlled by feedback based on the buffer level. A CBR transport over networks, result is a good performance compared with that of VBR. It introduced simplicity of network monitoringand analysis, where the VBR video streaming over CBR channel can be adapted to avoid the problem of congestion of the network. This paper studies the important issue of adapting VBR-compressed video for transport over a CBR channel. The developed systems are implemented using Matlab (Ver 6.5) underWindows XP operating system